Nursing students' experiences with the use of authentic assessment rubric and case approach in the clinical laboratories. (April 2015) - Wu, Xi Vivien; Heng, Mary Anne; Wang, Wenru
Summary: Background: One current challenge for nurse educators is to examine effective nursing assessment tools which integrate nursing knowledge into practice. Authentic assessment allows nursing students to apply knowledge to real-life experiences. Contextualized cases have engaged students for preparation of diverse clinical situations and develop critical thinking skills. Aim: This study aimed to explore nursing students' experiences and learning outcomes with the use of an authentic assessment rubric and a case approach. Methods: An exploratory qualitative approach using focus-group discussions and an open-ended survey was adopted. Sixteen nursing students participated in three focus-group discussions and 39 nursing students completed an open-ended survey. Results: Nursing students noted that an authentic assessment rubric with a case approach provided clarity for their learning goals; built confidence; developed knowledge, skill competencies and critical thinking skills; increased awareness of caring attributes and communication skills; and enriched and extended learning through self-, peer- and teacher-assessments. Conclusions: These findings provide rich insights for nurse educators and curriculum developers in the use of an authentic assessment rubric and a case approach in nursing education.